Teknologi Tepat Guna untuk Meningkatkan Kualitas dan Kuantitas Serta Jangkauan Pemasaran Ikan Kering Berbumbu di Desa Sletreng Kec. Kapongan, Kab. Situbondo - Indarto, Cahyo; Mojiono , Mojiono; Mu’tamar, M. Fuad Fauzul; Maflahah , Iffan; Supriyanto, Supriyanto (Proceedings of Annual Conference on Community Engagement, 2022)
Seasoned dried fish is one of the innovative products from conventional dried fish. There are many home industries of seasoned dried fish in Sletreng, a village in Kapongan District, Situbondo. Further development is required to eradicate undesirable characteristics such as greasy texture, high rancidity, and unattractive packaging. Consequently, these drawbacks alleviate consumer’s acceptance. To fill the gap, the use of appropriate technology is needed in order to improve product and packaging quality. In this regard, a spinner machine could be applied to reduce oil content, aiming to retard rancidity and enhance product’s appearance. The selection of packaging materials and design also determines the durability of the product and increases the attractiveness of the product; thereby, the acceptability of the product can reach broader market, especially accessed by using online marketing. The results showed that the proposed strategies successfully improved product acceptability as represented by higher sale volume and market.